Seasonality of Burkitt's lymphoma in Uganda - Muwazi, L (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND/AIMS: Burkitt's lymphoma is the most common childhood oral maxillofacial tumor in Africa and some studies have reported seasonal variation. MATERIALS AND METHODS: All Burkitt's cases diagnosed from 1969 to 2006, from all over Uganda, at the Makerere University's Department of Pathology, were analyzed, to determine seasonal variation. This was done by evaluation of monthly and rainy versus dry season prevalence. STATISTICAL ANALYSIS: The Wilcoxon test was used in both cases, to assess the statistical significance of differences in the diagnostic rates of Burkitt's lymphoma, in comparison to nonspecific chronic inflammation, using the total as the denominator. Yearly variation in prevalence was examined by a Chi-square test for linear trend. Mann-Whitney tests were done to compare the climatic regions. Multivariate analysis of variance (MANOVA) was used to test for differences when gender, seasons and climatic regions were factored in. RESULTS: Although monthly frequencies varied considerably over the period, none of the differences were statistically significant (Pearson's 15.199, degrees of freedom df = 11, P = 0.174). Likewise, there was no statistically significant difference in the total number of Burkitt's and nonspecific chronic inflammation biopsies handled at the Department during the rainy and dry seasons. CONCLUSION: Although the 38-year period gave us sufficient numbers to use the Edward's method for seasonality, it also meant that a lot of seasonal changes that occurred during the period were not taken into consideration. We hence feel that a review of this data with weather experts, so as to group the biopsies into accurate rainfall and dry patterns, would yield a more authoritative publication.